High Crystalline Dithienosilole-Cored Small Molecule Semiconductor for Ambipolar Transistor and Nonvolatile Memory - Kang, Woonggi; Jung, Minwoo; Cha, Wonsuk; Jang, Sukjae; Yoon, Youngwoon; Kim, Hyunjung; Son, Hae Jung; Lee, Doh-Kwon; Kim, BongSoo; Cho, Jeong Ho (American Chemical Society, 2014)
We characterized the electrical properties of a field-effect transistor (FET) and a nonvolatile memory device based on a solution-processable low bandgap small molecule, Si1TDPP-EE-C6. The small molecule consisted of electron-rich thiophene-dithienosilole-thiophene (Si1T) units and electron-deficient diketopyrrolopyrrole (DPP) units. The as-spun Si1TDPP-EE-C6 FET device exhibited ambipolar transport properties with a hole mobility of 7.3 X 10(-5) cm(2)/(V s) and an electron mobility of 1.6 X 10(-5) cm(2) /(V s). Thermal annealing at 110 degrees C led to a significant increase in carrier mobility, with hole and electron mobilities of 3.7 X 10(-3) and 5.1 X 10(-4) cm(2)/(Vs), respectively. This improvement is strongly correlated with the increased film crystallinity and reduced pi-pi intermolecular stacking distance upon thermal annealing, revealed by grazing incidence X-ray diffraction (GIXD) and atomic force microscopy (AFM) measurements. In addition, nonvolatile memory devices based on Si1TDPP-EE-C6 were successfully fabricated by incorporating Au nanoparticles (AuNPs) as charge trapping sites at the interface between the silicon oxide (SiO2) and cross-linked poly(4-vinylphenol) (cPVP) dielectrics. The device exhibited reliable nonvolatile memory characteristics, including a wide memory window of 98 V, a high on/off-current ratio of 1 X 10(3), and good electrical reliability. Overall, we demonstrate that donor-acceptor-type small molecules are a potentially important class of materials for ambipolar FETs and nonvolatile memory applications.
Keywords: FIELD-EFFECT TRANSISTORS; THIN-FILM TRANSISTORS; HIGH-PERFORMANCE; MATERIALS DESIGN; N-CHANNEL; POLYMER; ELECTRON; HOLE; SUBSTITUTION; MOBILITIES